The Future of Coaching Building Bridges Between Science and Practice - Greif, Siegfried; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book builds bridges between the science of coaching and coaching practice by analyzing the effects of coaching in detail and improving its practical effectiveness. Written by a proven expert in the field, it scrutinizes old and new methods of coaching and substantiates what still works and what does not. It provides guidance to silt the science from pseudoscience and charlatanism. Some of the topics it covers are: Simple and complex questioning methods, vision development, values analysis, strengths maps, narrative coaching, changing habits, executive communication, conflicts, stress management, burnout, health behavior, team coaching and coaching for organizational change (including e-coaching tools and artificial intelligence). The book collates the findings in an integrative, systemic theory of "result-oriented coaching" that is open to change, and addresses future developments in the coaching market, digitalization and artificial intelligent systems in coaching, with a plea for humanistic, science-driven and practice-based coaching. .
Building Bridges Between Science and Practice -- What is Coaching? -- Comparison of Coaching with other Methods -- Different types of Coaching -- Directions and concepts of coaching -- Coaching methods: Reappraisal under posttraditional scientific magnifying glass -- Examining Coaching Effectiveness -- Coaching processes -- Result-oriented Coaching -- Perspectives.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Personal coaching; Positive psychology; Psychology, Industrial; Coaching; Positive Psychology; Work and Organizational Psychology; Occupational Health Psychology